Students' Learning Experience with Kahoot in Arabic Language Instruction - Ervan Shodiq; Lili Musyafa’ah (Journal of Practice Learning and Educational Development, 2026)
Arabic language instruction at the Al-Iman Situbondo *Madrasah Diniyah Putra* (Islamic boarding school for boys) faces challenges stemming from low student interest and the perception that the subject matter is extremely difficult. This study aims to describe the role of Kahoot in transforming the students' learning experience. Employing a qualitative case study method, data were gathered through interviews, observations, and documentation involving six beginning-level students. The results indicate that integrating Kahoot successfully transformed the classroom atmosphere from monotonous to interactive and competitive, significantly boosting student motivation and focus. Despite obstacles related to digital literacy and device limitations, the gamification elements proved effective in mitigating instructional fatigue. In conclusion, the use of digital media can overcome students' cognitive resistance toward the Arabic language by fostering an enjoyable learning experience. These findings recommend the gradual digitalization of *pesantren* (Islamic boarding schools) to enhance the quality of language education.